The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1104/pp.102.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Membrane-Bound Inositol Phospholipid-Specific Phospholipase C from Suspension-Cultured Rice (Oryza sativa L.) Cells (Identification of a Regulatory Factor)

Abstract: A membrane-bound inositol phospholipid-specific phospholipase C was solubilized from rice (Oryza sativa L.) microsomal membranes and purified to apparent homogeneity using a series of chromatographic separations. l h e apparent molecular mass of the enzyme was estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis to be 42,000 D, and the isoelectric point was 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…With respect to biochemical characterizations of PIP 2 -PLC, it has been reported that Ca 2+ concentration, pH and protein concentration are among the most important affectors Pfaffmann et al, 1987;Pical et al, 1992;Yotsushima et al, 1993). The properties of PLC toward PIP 2 from pea leaves examined in this study (Fig.…”
Section: Article In Pressmentioning
confidence: 98%
“…With respect to biochemical characterizations of PIP 2 -PLC, it has been reported that Ca 2+ concentration, pH and protein concentration are among the most important affectors Pfaffmann et al, 1987;Pical et al, 1992;Yotsushima et al, 1993). The properties of PLC toward PIP 2 from pea leaves examined in this study (Fig.…”
Section: Article In Pressmentioning
confidence: 98%
“…We report here a kinetic study of the partially purified, membrane-associated enzyme using different approaches. Few reports regarding the biochemical characterization of plant PLC are available (Tate et al, 1989;Melin et al, 1992;Pical et al, 1992;Yotsushima et al, 1992Yotsushima et al, , 1993Hirayama et al, 1995;Huang et al, 1995;Shi et al, 1995;Kopka et al, 1998). To our knowledge, this is the first report in which different assays were used to characterize this enzyme in plants.…”
Section: Discussionmentioning
confidence: 99%
“…PLC is a family of isoenzymes that has been classified into three groups: ␤, ␥, and ␦ (Rhee and Bae, 1997). In plants several studies have reported the biochemical presence of this enzyme (McMurray and Irvine, 1988;Tate et al, 1989;Melin et al, 1992;Pical et al, 1992;Yotsushima et al, 1992Yotsushima et al, , 1993Huang et al, 1995;De Los Santos-Briones et al, 1997). Different genes for PLC have also been cloned (Hirayama et al, 1995(Hirayama et al, , 1997Shi et al, 1995;Yamamoto et al, 1995;Kopka et al, 1998), all of them resembling the ␦ type.…”
Section: Camentioning
confidence: 99%
“…As seen in Fig. 4, NPC4 showed very low activity for PIP 2 (Ͻ10% of PC-hydrolyzing activity), suggesting that NPC4 has different substrate selectivity from PI-PLC (32,33). Next, we analyzed the effect of divalent cations on the enzyme activity, since many plant phospholipases are characterized as Ca 2ϩ -dependent enzymes.…”
Section: Npc4 Encoded a Functional Pc-plc That Prefers Pc For The Submentioning
confidence: 99%